PENDAMPINGAN PENERAPAN HYGIENE DAN SANITASI PANGAN PADA KANTIN INSTITUSI PEMERINTAHAN KOTA PAREPARE - RUSLAN LA ANE; SYAMSUAR MANYULLEI; MUH. FAJARUDDIN NATSIR; WAHYULAN AMBOI; SITI CHAERANI FATIMAH APDIN (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
One of the efforts in ensuring the halal status of a food product is by applying the principles of hygiene and sanitation in food management places (TPP) such as canteens. The lack of data and information about canteens that apply the principles of food hygiene and sanitation in Parepare City is the rationale for conducting this community service program. For this reason, assistance is needed for TPP/Canteen in implementing safe and healthy food hygiene & sanitation. This program was in the form of training and assistance for managers and owners/sellers in canteens within government offices in Parepare city related to the implementation of hygiene and sanitation of safe and healthy TPP, which includes (a) making and distributing handbooks containing guidelines for self-assessment and self-supervising for hygiene & sanitation of the TPP, (b) counseling and training on the implementation food management places, especially in canteens within government institutions in Parepare city, also (c) assistance in submission for labeling of being supervised and monitored for canteens who have met health requirements for healthy canteens in institution setting. Food management places (TPP), especially in canteens within government office in Parepare city, must become a role model in the implementation of safe and healthy food hygiene & sanitation principles in order to support the implementation plan of the Halal Product Guarantee System program in Parepare city. ABSTRAKSalah satu upaya dalam menjamin kehalalan suatu produk pangan yaitu dengan menerapkan prinsip-prinsip hygiene dan sanitasi pada tempat-tempat pengelolaan pangan (TPP) / kantin. Masih minimnya data dan informasi mengenai kantin yang menerapkan prinsip-prinsip hygiene dan sanitasi pangan di Kota Parepare menjadi dasar pemikiran pelaksanaan program pengabdian kepada masyarakat ini. Untuk itu dibutuhkan pendampingan bagi TPP/Kantin dalam menerapkan hygiene dan sanitasi pangan yang aman dan sehat. Kegiatan ini berupa pelatihan dan pendampingan bagi pengelola kantin yang ada di kantor-kantor pemerintahan kota Parepare terkait penerapan hygiene dan sanitasi TPP yang aman dan sehat, meliputi (a) pembuatan dan pembagian buku saku berisi panduan penilaian dan pengawasan hyigene & sanitasi TPP secara mandiri, (b) penyuluhan dan pelatihan penerapan hygiene & sanitasi TPP pada kantin atau sejenisnya yang aman dan sehat, serta (c) pendampingan pengajuan label pengawasan/pembinaan bagi pengelola kantin yang telah memenuhi syarat kesehatan di kantor-kantor pemerintahan Kota Parepare. Tempat pengelolaaan pangan khususnya pada kantin di kantor-kantor lingkup pemerintahan Kota Parepare harus menjadi contoh penerapan prinsip-prinsip hygiene dan sanitasi pangan yang aman dan sehat guna mendukung rencana penerapan program Sistem Jaminan Produk Halal di Kota Parepare.